Renal Safety of Long-Term Antihypertensive Therapy: A Systematic Review - Thendi Abdul Arief; Yohanna Lawanda da Costa; Niky Budiarti; Luthfiah Pertiwi; Agung Endro Nugroho; Zullies Ikawati (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
Background: Managing hypertension, a major risk factor for chronic kidney disease (CKD), requires long-term antihypertensive medication. However, clinical judgment and medication adherence are impacted by ongoing worries about its renal safety.Objectives: This study aimed to systematically evaluate and compare the renal safety profiles of antihypertensive drug classes during long-term use (>6 months) in hypertensive patients.Methods: Following the PRISMA 2020 principles, a systematic review was carried out. A thorough search of PubMed and ScienceDirect from 2015 to April 2025 was conducted (